The books of the Maccabees : history, theology, ideology : papers of the Second International Conference on the Deuteronomical Books, Papa, Hungary, 9-11 June, 2005 - Xeravits, Geza G.; Zsengeller, Jozsef. (Supplements to the Journal for the Study of Judaism, 2007)
This volume publishes papers delivered at the Second International Conference on the Deuterocanonical Books (Pápa, Hungary). This conference dealt with the Books of the Maccabees. As such, this was the most extended discussion of these books that ever took place at a scholarly meeting. The volume contains articles on the textual forms, traditions, theology and ideology of the books, and demonstrates the books' relationship with the contemporary literature of early Judaism.